Eat a little and save a little: A qualitative exploration of acceptability of a potential savings intervention to reduce HIV risk among female sex workers in Western Kenya. - Sophie Otticha; Jane Moraa; Jacob Onyango; Olivia Okumu; Marylyn Ochillo; Judith Ayallo; Phillip Owiti; Lillian Ouma; Nancy Ounda; Tobias Odwar; Shantana Carol Ogot; Kawango Agot (PLoS ONE)
Background The burden of HIV among female sex workers (FSWs) remains higher in sub-Saharan Africa (SSA), with an estimated prevalence of 36.9%. In Kenya, HIV prevalence among FSWs is 29.3% compared to 6.6% among adult women in the general population. Economic disempowerment is a significant driver of HIV among FSWs, specifically manifested in engagement in higher-paying, high risk sex. Saving interventions to improve financial security have the potential to reduce HIV risk among FSWs. Methods We conducted 24 focus group discussions (FGD) with each session involving 6-10 respondents. The FGD guide explored saving history and income sources, spending and loan-taking practices as factors associated with saving. Thematic analysis identified themes related to financial burden, loaning, saving and spending, sources of income, HIV risk behaviors in the context of sex work, and acceptability of the proposed saving intervention to reduce HIV risk. Results We conducted 24 FGDs with 221 respondents, of whom 19.9% were married and 85.4% reported being heads of households. We identified the following key themes, that FSWs were: open to participating in a saving intervention being proposed to reduce their HIV risk; financially insecure, thus engaging in sexual practices that increase their HIV risk; living beyond their means leading to further financial insecurity; and desiring an intervention that equips them with knowledge and skills on how to balance earning and spending in order to save and how to take and repay loans without increasing their HIV risk. Conclusion FSWs in western Kenya were receptive to the proposed savings intervention, believing that it would increase their financial stability and reduce the need to engage in risky sex when faced with emergency situations that require immediate cash.